2020
DOI: 10.3892/mco.2020.1996
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting pathological upgrading after prostatectomy in patients with Gleason grade group 1 prostate cancer based on opinion‑matched biopsy specimens

Abstract: The present study investigated the concordance between Gleason scores assigned to prostate biopsy specimens by outside pathologists and a urological pathology expert, and determined the risk of upgrading between opinion-matched Gleason grade group (GGG) 1 biopsy specimens and radical prostatectomy specimens. Between January 2012 and May 2018, 733 patients underwent robot-assisted radical prostatectomy. Patients whose original biopsy specimens from outside hospitals were reviewed by a urological pathology exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…A discordant GG between needle biopsy and final pathology is associated with interobserver variability among different pathologists, borderline grades, and more significantly sampling errors 26 . In support of these arguments, Maruyama et al reported that GG concordance improved by 6.2% after second-opinion pathology 27 .…”
Section: Discussionmentioning
confidence: 88%
“…A discordant GG between needle biopsy and final pathology is associated with interobserver variability among different pathologists, borderline grades, and more significantly sampling errors 26 . In support of these arguments, Maruyama et al reported that GG concordance improved by 6.2% after second-opinion pathology 27 .…”
Section: Discussionmentioning
confidence: 88%
“…[ 19 ] Numerous publications showed that mandatory second opinion pathology review by specialized urological pathologists leads to alteration of the management strategy and improved care in some cases. [ 3 7 8 11 20 ] The accuracy of the GS in NCB specimens depends on the experience in uropathology and workload of the reviewing pathologist. [ 3 ] A major discrepancy in the GS assigned by general versus specialized pathologists occurs in 15%–41% of NCB specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing the number of biopsy cores improves both sampling and accuracy. [ 11 ] Conversely, a small number of biopsy cores with a shorter length might lead to the overestimation of the GGG in NCB specimens. Another way to reduce sampling error is to improve tumor visualization and targeting during the biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At smaller facilities, the diagnosis is not always made by experienced pathologists. Although diagnosis by experienced urological pathologists provides a more accurate GG assessment than inexperienced pathologists [14][15][16], only a few cases are available to verify whether reassessments are truly beneficial for the patient [17]. As our institution is a high-volume institution with experienced urological pathologists, we often reassess specimens from other institutes.…”
Section: Introductionmentioning
confidence: 99%